Kajian Perilaku Penghuni Bangunan Hunian Saat Menghadapi Gempa Banda Aceh 2004 - Ulfa Mazaya; Alfikhairina Jamil; Sri Batara Nurfajri Arisaputri; Atika Aditya (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Indonesia is a disaster-prone country, particularly to earthquakes, which often occur suddenly and cause significant damage. This study aims to understand the behavior of residents in residential buildings during the major earthquake in Banda Aceh in 2004. The research adopts an exploratory qualitative approach, with data collected through open-ended online questionnaires. The analysis reveals various behavioral patterns during the disaster, including staying outside the building, helping others, staying inside the building, evacuating, protecting oneself, following others, heading to a building, praying, and not taking any action. Demographic factors such as age and gender influenced individual responses, especially the tendency for children to follow adults in decision-making. The findings highlight that earthquake response behaviors vary greatly, influenced by environmental, demographic, and emergency factors, and underscore the importance of building design that supports quick and safe evacuation.